Synthesis and mechanical properties of lanthanum oxide (La 2O3)doped 8 mol % yttria-stabilized cubic zirconia (8YSZ) - (:unkn) unknown (My University, 2012)
In this study, 8 mol % yttria stabilized cubic zirconia (8YSZ) powders as a matrix material and 0-15 wt% La2O3 powders as an additive were used in order to determine the effect of La2O3 addition and amount on the phase stability, microstructure and mechanical properties of 8YSZ. XRD results showed the existence of cubic and hexagonal crystal structures for all addition amounts. Besides, La2O 3 up to 5 wt% was completely dissolved in the crystal structure of 8YSZ but, La2O3 with higher than 5 wt% reacted with 8YSZ at high temperatures and formed pyrochloric La2Zr2O 7 compound. The hardness values of 8YSZ decreased and fracture toughness increased with the increase in La2O3 amount. © 2012 IEEE.
Keywords: cubic zirconia; fracture toughness; hardness; La 2Zr2O7; La2O3